2020
DOI: 10.1108/jamr-03-2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest supply chain losses: a state-of-the-art literature review and bibliometric analysis

Abstract: PurposeThe literature review of post-harvest supply chain (PHSC) losses is carried out and analyzed in this paper followed by bibliometric analysis of the literature.Design/methodology/approachThe literature survey is performed across various dimensions such as PHSC losses, PHSC risks and PHSC sustainability (waste management and waste reduction). One hundred thirty research articles during the period of 1989–2020 were considered for the review.FindingsThe PHSC losses have been identified in this literature su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…The implementation of vertical integration will not only improve product availability and marketability but will also reduce produce spoilage at supply chain junctions and supply chain costs in the developing nations. The concerns for market prospects and rural employability via vertical integration will improve by working upon strategic and tactical frontier initiatives (Whipple and Gentry, 2000; Deakins et al , 2016; Priyadarshi et al , 2019; Priyadarshi et al , 2020). The reliability test results indicated that the selected PHCEs pose a significant impact on rural produce marketability, rural employment and business sustainability with vertical integration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The implementation of vertical integration will not only improve product availability and marketability but will also reduce produce spoilage at supply chain junctions and supply chain costs in the developing nations. The concerns for market prospects and rural employability via vertical integration will improve by working upon strategic and tactical frontier initiatives (Whipple and Gentry, 2000; Deakins et al , 2016; Priyadarshi et al , 2019; Priyadarshi et al , 2020). The reliability test results indicated that the selected PHCEs pose a significant impact on rural produce marketability, rural employment and business sustainability with vertical integration.…”
Section: Discussionmentioning
confidence: 99%
“…The CFA was used to observe the model fit with the help of empirical data (Zahay and Griffin, 2010; Ferro et al , 2017). The PHSCEs to be worked upon to improve market prospects and rural employability via vertical integration as strategic initiatives are ITR, IIV, TII, ASC, EDS and EFS (Kononets and Treiblmaier, 2020; Priyadarshi et al , 2020). The initiatives to be worked upon as tactical initiatives are DVI, AOW, TAA and GIV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lezoche et al [106] examined the future of agri-food and asserted that adopting new technologies would improve various components of the system. Priyadarshi et al [107] reviewed postharvest supply chain losses. Articles published between 1989 and 2020 were considered in this review paper.…”
Section: Review Papersmentioning
confidence: 99%